Identifying multiple interacting bad data in power system state estimation - Asada, Eduardo N.; Garcia, Ariovaldo V.; Romero, R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
This paper presents an intelligent search strategy for the conforming bad data errors identification in the generalized power system state estimation, by using the tabu search meta heuristic. The main objective is to detect critical errors involving both analog and topology errors. These errors are represented by conforming errors, whose nature affects measurements that actually do not present bad data and also the conventional bad data identification strategies based on the normalized residual methods. ©2005 IEEE.
Keywords: Data reduction; Errors; Heuristic methods; Identification (control systems); Strategic planning; Topology; Data errors; Meta heuristics; Power system; Topology errors; Electric power systems